2021
DOI: 10.1017/jns.2021.81
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of dehydration state and fluid intake practice among adults population in the Jazan Region of Saudi Arabia, 2019

Abstract: Despite the hot climate and high humidity in the Jazan Region of Saudi Arabia, which increases risk for dehydration, no previous studies have assessed awareness of dehydration and fluid intake practice among adults in this region. Therefore, the aim of this cross-sectional study was to determine awareness of the dehydration state and fluid intake practices among 440 adults in the Jazan Region of Saudi Arabia. Out of the total, 51⋅8 % were male and 48⋅2 % were females. Good knowledge of dehydration definition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…CL wearing may result in corneal and conjunctival complications secondary to hypersensitivity reactions, hypoxic changes, mechanical trauma, and infection [ 29 ]. In accordance with the literature, the most common CL-related adverse effects reported in this study were eye redness and dryness [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…CL wearing may result in corneal and conjunctival complications secondary to hypersensitivity reactions, hypoxic changes, mechanical trauma, and infection [ 29 ]. In accordance with the literature, the most common CL-related adverse effects reported in this study were eye redness and dryness [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…In keeping with this, most of the participants in the current study never shared their CLs with others, which plays a part in decreasing the risk of CL-related infections CL wearing may result in corneal and conjunctival complications secondary to hypersensitivity reactions, hypoxic changes, mechanical trauma, and infection [29]. In accordance with the literature, the most common CL-related adverse effects reported in this study were eye redness and dryness [11].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Aswad and Loleh showed that in Indonesia, PPE utilization among nurses affected urine color significantly due to heat and low intake of water during PPE utilization ( 30 ). Participants with the highest level of PPE utilization might be aware of their condition where they experienced higher risk of dehydration as Albasheer et al showed that people who lived in hot climate and high humidity country displayed good dehydration state awareness ( 31 ). Consequently, the situation where higher awareness was shown enforce the workers to comply fluid intake recommendation ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also has a population of about 1.6 million, as per the 2018 census. [ 16 ] The study employed male and female students from health-related colleges at Jazan University, which includes 26 colleges and more than 50,000 students. Students were randomly selected from the Faculties of Medicine, Dentistry, Applied Medical Sciences, Public Health and Tropical Medicine, Nursing and Health Sciences, and Pharmacy.…”
Section: Methodsmentioning
confidence: 99%